Genome-wide association studies in plants: the missing heritability is in the field - Brachi, Benjamin (BioMed Central, 2011)
Genome-wide association studies (GWAS) have been even more successful in plants than in humans. Mapping approaches can be extended to dissect adaptive genetic variation from structured background variation in an ecological context.